2011
DOI: 10.1097/tp.0b013e318224c109
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Bronchiolitis Obliterans Syndrome Risk Monitoring in Lung Transplant Recipients

Abstract: Monitoring the bronchoalveolar lavage fluid levels of seven polypeptides detected by matrix-assisted laser desorption/ionization time-of-flight mass spectrometry allows a reliable prediction of early BOS using a Random Forest decision tree-based classifier model. The high accuracy of this robust model and its synergistic potential in combination with established forced expiratory volume-based diagnostics could make it an effective tool to supplement the current diagnostic regime after multicentric validation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 44 publications
(42 reference statements)
0
9
1
Order By: Relevance
“…All of these groups, however, had higher BAL CCSP levels than those in BOS. This suggests that CCSP, while reduced in BOS, may be less useful as a biomarker for early disease identification, in contrast to the preliminary results observed in the prior studies (10–13). In part, these results might reflect the primarily cross‐sectional nature of our study (15).…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…All of these groups, however, had higher BAL CCSP levels than those in BOS. This suggests that CCSP, while reduced in BOS, may be less useful as a biomarker for early disease identification, in contrast to the preliminary results observed in the prior studies (10–13). In part, these results might reflect the primarily cross‐sectional nature of our study (15).…”
Section: Discussioncontrasting
confidence: 78%
“…Due to the pilot nature of that study, however, confirmation of the proteins identified in the MALDI‐TOF profile was not performed. More recently, Wolf and colleagues generated BAL proteome profiles for 82 lung transplant recipients, 48 of whom developed BOS (12). Among the panel of significant markers was CCSP; however, this finding was validated by ELISA in only 13 patients, 8 of whom had BOS.…”
Section: Discussionmentioning
confidence: 99%
“…Peroxiredoxin II was found to be exclusively expressed in BOS, whereas surfactant protein A displayed significantly lower expression in BOS patients compared to stable controls [70]. Based on a panel of seven statistically significant polypeptide markers, Wolf et al established a predictor model to detect BOS-related proteome changes in BALF before its clinical diagnosis [71]. …”
Section: Lung Transplantationmentioning
confidence: 98%
“…Treatment is limited to immunosuppressant augmentation to which response is poor and five-year survival after diagnosis is only 30-40% [2]. While single proteins, such as human neutrophil defensin, MMP-9, surfactant protein A, and unique peptides have previously been identified that correlate with the development of BOS, the global longitudinal changes in proteins and their associated biological processes in the development of BOS have not been described [3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%